Enhancing Mental Health Care Through Psychoreligious Intervention: Qur’anic Murottal Therapy for Substance Abuse Patients in a West Java Rehabilitation Unit - Bagja Angga Sukma; Muhammad Ali Nurzaini; Irfan Zakaria (STIKes Budi Luhur Cimahi, 2026)
Anxiety is a psychological symptom experienced by patients with substance use disorders, which may occur both during substance use and throughout the withdrawal process. Substance abuse is often associated with various health issues, including mental health disorders such as anxiety and depression, which further diminish patients’ quality of life. Furthermore, elevated anxiety levels among individuals with substance use disorders increase the risk of relapse and rehabilitation failure. In this context, psychoreligious therapy through listening to Quranic murottal has emerged as a potential alternative for managing anxiety in individuals with substance use disorders. This study aimed to investigate the effect of Quranic murottal psychoreligious therapy on reducing anxiety levels in patients undergoing rehabilitation at the West Java Provincial Mental Hospital. A quasi-experimental design with a pretest-posttest control group approach was used. A total of 28 respondents were selected through total sampling. The study demonstrated a significant effect of Quranic murottal therapy in reducing anxiety levels among patients with substance use disorders, with an average decrease of 13.143 points. Statistical analysis showed a p-value of 0.000, which is lower than the significance threshold of 0.05 (p < 0.05). Additionally, a significant difference in anxiety levels was also observed in the control group (p = 0.02 < 0.05). The findings indicate that Quranic murottal psychoreligious therapy significantly reduces anxiety levels in patients with substance use disorders. These results are expected to contribute to the implementation of spiritual care interventions in the substance use rehabilitation ward.